2017
DOI: 10.18196/jgpp.4170
|View full text |Cite
|
Sign up to set email alerts
|

Konsistensi Perencanaan Pembangunan Daerah Dengan Anggaran Daerah

Abstract: Development in Indonesia so far has achieved planning approach. Based on Law No. 17 Year 2003 on State Finance Regional Budget that contained in the budget based on the RKPD, and the mandate of Law Number 25 Year 2004 on National Development Planning System, states that the planning process should be through participatory musrenbang. The planning process in Gunung Kidul Regency musrenbang promote participatory, although it has been difficult to realize the consistency, and the problems in the development gaps … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 0 publications
0
7
0
4
Order By: Relevance
“…On the other hand Fikri et al (2015), concluded that, to realize careful planning, the involvement of all stakeholders was needed. In connection with the importance of supervision, in the study of Sugiarto (2015), stated that, "Factors that influence consistency are Understanding between LD; the existence of central policy; the evaluation of the Local Annual Budget Planning by the Governor; and contained the main thoughts of the Local Representatives into the LD activities program. "…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand Fikri et al (2015), concluded that, to realize careful planning, the involvement of all stakeholders was needed. In connection with the importance of supervision, in the study of Sugiarto (2015), stated that, "Factors that influence consistency are Understanding between LD; the existence of central policy; the evaluation of the Local Annual Budget Planning by the Governor; and contained the main thoughts of the Local Representatives into the LD activities program. "…”
Section: Resultsmentioning
confidence: 99%
“…Regional development is one of the efforts aimed at building harmony and balance of development between regions by their natural potential and utilizing this potential efficiently, orderly, and safely. Regional development is needed as the development of space to advance the area from various sectors (Sugiarto and Mutiarin, 2016). Regional development is a development that covers various sectors, including infrastructure.…”
Section: Pleminarymentioning
confidence: 99%
“…(Siswanto, 2011) Pandangan baru pembangunan yaitu penghapusan kemiskinan, ketimpangan, dan pengangguran dalam konteks pertumbuhan ekonomi. Menurut (Sugiarto & Mutiarin, 2017) pandangan baru pembangunan mulai dari proses dalam pelaksanaannya harus mempunyai tiga nilai inti serta tujuan. Menurut (Sugiarto & Mutiarin, 2017) ketiga nilai inti pembangunan adalah : 1) Kemampuan untuk memenuhi kebutuhan dasar (sustenance); 2) Manusia terhormat dalam bentuk harga diri; 3) Kebebasan (freedom of servitude).…”
Section: Metode Penelitianunclassified
“…Menurut (Sugiarto & Mutiarin, 2017) pandangan baru pembangunan mulai dari proses dalam pelaksanaannya harus mempunyai tiga nilai inti serta tujuan. Menurut (Sugiarto & Mutiarin, 2017) ketiga nilai inti pembangunan adalah : 1) Kemampuan untuk memenuhi kebutuhan dasar (sustenance); 2) Manusia terhormat dalam bentuk harga diri; 3) Kebebasan (freedom of servitude). Adapun tiga tujuan pembangunan adalah: 1) Peningkatan ketersediaan seerta perluasan distribusi barang kebutuhan pokok; 2) Peningkatan standar hidup; 3) Perluasan pilihan ekonomis dan sosial bagi setiap individu.…”
Section: Metode Penelitianunclassified